Inhibitory effect of esculentoside A on prostaglandin E2 production from murine peritoneal macrophages and rabbit synovial cells in vitro - H-B. Wang; J. Fang; Q-Y. Zheng (Hindawi Limited, 1997)
Esculentoside A (EsA) is a saponin isolated from the roots of Phytolacca esculenta. Previous experiments have shown that it has strong antiinflammatory effects. To investigate the mechanism of anti-inflammatory effects of esculentoside A (EsA),[3H] arachidonic acid (AA) prelabelled murine macrophage and radioimmunoassay were used to test the effect of EsA on the total release of AA and prostaglandin E2 in culture supernatants. The results showed that EsA had no significant effect on the total release of AA from murine macrophages. EsA (2.5-10 μmol/l), from unstimulated murine peritoneal macrophages and rabbit synovial cells, could decrease the production of prostaglandin E2. In A23187 and LPS-treated macrophages and synovial cells, EsA (10 μmol/l) could significantly decrease the prostaglandin E2 production. These results confirmed that EsA exerted an inhibitory effect on prostaglandin E2 production from murine macrophages and rabbit synovial cells.